Lack of Financial Reporting Using Crowe’s Fraud Pentagon Theory - Koharudin, Alif; Januarti, Indira (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
Research purposes: This paper examines factors affecting fraudulent financial reporting based on Crowe’s fraud pentagon theory. Pentagon theory elements include pressure (financial stability, financial target, external pressure), opportunity (the independent board of commissioners), rationalization (change in auditor), competence (director change), arrogance (frequent number of directors’ display picture in the annual report).Methods: This study used secondary data gathered from annual reports and financial reports of companies in the manufacturing sector listed on the Indonesia Stock Exchange during 2015-2019. Data analysis method tested using logistic regression analysis.Results: The results showed that financial stability and auditor change effects on fraudulent financial reporting. Results also show that financial target, external pressure, independent board of commissioners, directors change, and a frequent number of director’s display picture in an annual report does not affect the fraudulent financial reporting.Novelty: The combination of using pentagon theory with Beneish M-Score as a prediction of financial statement fraud. The contribution of this research is to provide input to report’s users to pay attention to pressure and rationalization factors in fraudulent financial reporting.